The Role of Media Relations and Information Disclosure in the Positive Image of the South Tangerang Police - Intany Pradisya; Yulia Rahmawati; Novi Andayani Praptiningsih (Journal of Research in Social Science and Humanities, 2025)
This study aims to discuss the role of media relations and information disclosure in building a positive image of the South Tangerang Police. In the digital age, police public relations are not only required to convey information, but also to manage public perception through communication strategies that are transparent, participatory, and adaptive to technology. Using a qualitative approach based on a literature review, this study analyzes the communication strategies of the South Tangerang Police Public Relations Department through the use of social media and partnerships with local media. The results show that the success of building a positive image of the police is determined by a combination of information transparency, the use of digital technology, the strengthening of media relations, and the strategic management of negative issues. However, challenges such as disinformation, trust deficits, and resource constraints remain obstacles that must be anticipated. Therefore, communication innovation, digital literacy, and continuous evaluation are important factors in strengthening the legitimacy and public trust in police institutions.